Microsporidia detection and genotyping study of human pathogenic E. bieneusi in animals from Spain. - Ana Luz Galván-Díaz (Public Library of Science (PLoS), 2014)
Microsporidia are ubiquitous parasites infecting all animal phyla and we present evidence that supports their zoonotic potential. Fecal samples taken from domestic (cats and dogs), farm (pigs, rabbits and ostriches) and wild animals (foxes) from different provinces of Spain were evaluated for microsporidia infection by light microscopy and PCR. After Microsporidia species identification, E. bieneusi genotypes were additionally studied by sequence analysis of the ITS region. Eighty-five samples out of 159 exhibited structures that were compatible with microsporidia spores by Webeŕs stain with 37 of them being confirmed by PCR. Microsporidia species identified included E. bieneusi, E. intestinalis and A. algerae. We report the first diagnosis of E. intestinalis and E. bieneusi in ostriches and A. algerae in pigs. We also provide new information on the molecular characterization of E. bieneusi isolates both in rabbits and ostriches. All of the E. bieneusi genotypes identified belonged to the zoonotic group of genotypes (Group I) including genotypes A (dogs), I (pigs), D (rabbits and foxes) and type IV (ostriches). Our results demonstrate that microsporidia are present in domestic, farm and wild animals in Spain, corroborating their potential role as a source of human infection and environmental contamination.